The Effect of Desensitizing Agent on Shear Bond Strength to Dentin using Three Self-etching Bonding Systems at Different Time Intervals. An In Vitro Study - Al-Chalabi, Ashraf S.; Taher, Rajaa; Chakmakchi, Makdad (Open Access Macedonian Journal of Medical Sciences, 2022)
Objectives: To investigate the shear bond strength of dentin surfaces using different self-etching bonding systems after treating with a desensitizing agent at different time intervals. Materials and methods: 63 sound upper premolars were used, the ‎occlusal aspect was sectioned at the middle in a ‎vertical direction into buccal and ‎palatal halves. Each ‎specimen was mounted and a flat dentin surface was ‎prepared at the middle third of each specimen. The sectioned samples were divided into 3 groups according to the bonding agent n=42. One-half of each tooth was treated with desensitizing agent Quadrant FiniSense then both halves were bonded with one of the three self-etching bonding systems (G-Premio bonding‎, i Bond, Clearfil S3 bound plus). ‎After adhesive procedures, a composite resin was applied against the tooth to form ‎a cylinder ‎(2mm×4mm) and cured. From each group 14 specimens were stored in distilled water at 37° C for 24 ‎hours, 7 days, and 72 days. At the end of each interval, the samples were tested for the shear bond strength using a universal testing machine (Instron). Data were analyzed using the Independent t-test and One Way ANOVA Test and Duncan’s Multiple Range Test. Results: All bonding systems showed lower bonding strength when samples were treated with desensitizer with a significant difference at all time intervals except for the i bond group which showed no significant difference in bond strength at a period of 7 and 72 days in treated and without desensitizer treated samples. Conclusion: Obliteration of dentinal by dentin desensitizer may have a negative effect on the bonding strength of the self-etching bonding systems.